2016
DOI: 10.1111/mpp.12447
|View full text |Cite
|
Sign up to set email alerts
|

Plum pox virus capsid protein suppresses plant pathogen‐associated molecular pattern (PAMP)‐triggered immunity

Abstract: The perception of pathogen-associated molecular patterns (PAMPs) by immune receptors launches defence mechanisms referred to as PAMP-triggered immunity (PTI). Successful pathogens must suppress PTI pathways via the action of effectors to efficiently colonize their hosts. So far, plant PTI has been reported to be active against most classes of pathogens, except viruses, although this defence layer has been hypothesized recently as an active part of antiviral immunity which needs to be suppressed by viruses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 96 publications
(134 reference statements)
2
79
0
7
Order By: Relevance
“…One of the best studied PRRs in mammals, Toll-like receptors (TLR), have important roles in antiviral defense via recognition of a different range of MAMPs, such viral RNA and DNA (Song and Lee, 2012). In contrast, the PTI pathway in plants remains unclear with regard to resistance against viruses, although studies describing an association of PTI in antiviral immunity have been recently reported (Yang et al, 2010; Kørner et al, 2013; Nicaise, 2014; Machado et al, 2015; Nicaise and Candresse, 2016; Niehl et al, 2016). Indeed, a complex set of typical PTI responses is induced in plants upon virus infection, including SA accumulation, ROS production, ion fluxes, defense gene (e.g., PR-1) activation, and callose deposition (for a review, see Nicaise, 2014).…”
Section: Pamp-triggered Immunity In Antiviral Defenses: Co-receptors mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the best studied PRRs in mammals, Toll-like receptors (TLR), have important roles in antiviral defense via recognition of a different range of MAMPs, such viral RNA and DNA (Song and Lee, 2012). In contrast, the PTI pathway in plants remains unclear with regard to resistance against viruses, although studies describing an association of PTI in antiviral immunity have been recently reported (Yang et al, 2010; Kørner et al, 2013; Nicaise, 2014; Machado et al, 2015; Nicaise and Candresse, 2016; Niehl et al, 2016). Indeed, a complex set of typical PTI responses is induced in plants upon virus infection, including SA accumulation, ROS production, ion fluxes, defense gene (e.g., PR-1) activation, and callose deposition (for a review, see Nicaise, 2014).…”
Section: Pamp-triggered Immunity In Antiviral Defenses: Co-receptors mentioning
confidence: 99%
“…Consistently, Arabidopsis bak-1 mutants show increased susceptibility to three different RNA viruses, and crude extracts of virus-infected leaf tissues induce typical PTI responses in a BAK1-dependent manner (Kørner et al, 2013). The Arabidopsis double mutant bak1-5 bkk1 displays increased viral accumulation when inoculated with Plum pox virus (PPV; Nicaise and Candresse, 2016). Furthermore, MAPK4, a negative regulator of plant PTI signaling, suppresses soybean defense against Bean pod mottle virus (BPMV; Liu et al, 2011), and chitosan, a deacetylated chitin derivative elicitor, is able to stimulate the plant immune response against viruses (Iriti and Varoti, 2014).…”
Section: Pamp-triggered Immunity In Antiviral Defenses: Co-receptors mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few recent publications indicate that the known PTI components are involved in dsRNA recognition and that the reaction is an immune response distinct from the RNA silencing pathway. Therefore, these studies claim that PTI against viral pathogens is preserved in plants and animals (Korner et al, 2013; Nicaise, 2014; Nicaise and Candresse, 2016; Niehl et al, 2016). However, there is no direct evidence to explain how dsRNAs are recognized in plants; therefore, further studies are needed to determine whether an animal-like mechanism underlies dsRNA-mediated PTI in plants.…”
Section: Rna Silencing In Viral Defensementioning
confidence: 99%
“…PTI against viral pathogens has been primarily described in mammalian cells, but not in plant cells (Calil and Fontes, 2016). However, several recent studies provided evidence that PTI and related components are also involved in antiviral defense responses in plants (Korner et al, 2013; Nicaise, 2014; Iriti and Varoni, 2015; Calil and Fontes, 2016; Nicaise and Candresse, 2016; Niehl et al, 2016). In general, plants defense responses triggered against viral pathogens are based on RNA- or protein-mediated resistance.…”
Section: Introductionmentioning
confidence: 99%